1997
DOI: 10.1136/jnnp.63.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of psychological interventions for people with poorly controlled epilepsy

Abstract: People with epilepsy are at increased risk of anxiety and depression, of experiencing low self esteem, and of suVering from the stigma attached to having epilepsy. A recent, large community study (based on responses by 696 adults)1 showed the importance of frequency of current seizures in determining anxiety, depression, and perceived life fulfilment. Factors other than frequency of seizures may influence ability to cope psychologically.2 In addition, psychological factors have become increasingly recognised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Our results highlight that screening and management of suicide risk and mental health extend beyond those with treatment-resistant forms to those with wellcontrolled epilepsy. To date, the majority of psychological treatment trials have focused on those with refractory conditions [49,50]. Our findings, therefore, also call for greater research and clinical efforts to be made for those with well-controlled conditions [51].…”
Section: Strengths and Implicationsmentioning
confidence: 62%
“…Our results highlight that screening and management of suicide risk and mental health extend beyond those with treatment-resistant forms to those with wellcontrolled epilepsy. To date, the majority of psychological treatment trials have focused on those with refractory conditions [49,50]. Our findings, therefore, also call for greater research and clinical efforts to be made for those with well-controlled conditions [51].…”
Section: Strengths and Implicationsmentioning
confidence: 62%
“…Significant differences (*) were only observed in the Experimental Group. V = verbal scale, P = performance scale treatment of many psychiatric conditions, such as in ADHD Butnik 2005;Fox et al 2005;Fuchs et al 2003;Leins et al 2007;Levesque et al 2006;Linden et al 1996;Lubar and Lubar 1999;Lubar et al 1985;Lubar et al 1995a, b;Monastra et al 2002Monastra et al , 2005Nash 2000;Penberthy et al 2005;Pop-Jordanova et al 2005;Rossiter 2004a, b;Thompson and Thompson 1998), anxiety (Abarbanel 1999;Hammond 2005;Moore 2000), and affective disorders (Baehr et al 1999;Hammond 2005;Rosenfeld 2000), as well as in the treatment of addictions (Trudeau 2000), mainly alcoholism (Kelley 1997;Peniston and Kulkosky 1999), and neurological disorders, such as epilepsy Goldstein 1997;Lubar and Bahler 1976;Seifert and Lubar 1975;Sterman 2000;Sterman and Egner 2006;Sterman and Friar 1972;Walker and Kozlowski 2005) and traumatic brain injury (Ponsford and Kinsella 1998;Stamatina and Lubar 2004;Tinius and Tinius 2000). However, to the best of our knowledge, only one study considering exclusively LD children has been previously reported .…”
Section: Discussionmentioning
confidence: 98%
“…Most studies have focused on psychosocial failures (Gramstad et al, 2001;Suurmeijer et al, 2001;Tedman et al, 1995), suggesting that a generic psychological support or psychotherapy may help to overcome psychosocial handicaps and seizure-related distress (Goldstein, 1997;Mittan, 2009). CR focusing on specific cognitive impairments has been used to complement clinical care.…”
Section: Why Cognitive Rehabilitation In Epilepsy?mentioning
confidence: 99%